Pericardial Drain Placement in Interventional Radiology: An Overview - Herren, Josi L.; Chan, HingKui; Ray, Charles E., Jr. (Seminars in Interventional Radiology, 2022)
Pericardial effusions can occur from multiple different etiologies. Although often incidentally noted or clinically silent, pericardial effusions may cause significant hemodynamic compromise. In some of these patients, pericardiocentesis may be temporizing only and either repeat procedures or placement of pericardial drains may be preferable. While cardiologists typically perform pericardial drain placement, it is a procedure that may also be performed by interventional radiologists. This article describes for the interventional radiologist the indications and placement technique, as well as potential complications occurring from pericardial drain placement.
Keywords: interventional radiology; pericardial effusion; tamponade; drainage; pericardiocentesis